Identifying revealed comparative advantages in an EU regional context - Alexander Cordes; Birgit Gehrke; Roman Römisch; Christian Rammer; Paula Schliessler; Pia Wassmann (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2015)
[Introduction ...] Overall, this report is structured as follows: the next chapter (2) briefly outlines the relevance of regional trade indicators for determining the competitiveness of a region. In chapter 3, the methodology for the calculation of regional trade performance indicators is introduced, and the elementary results are described. Chapter 4 presents an econometric analysis relating key regional characteristics to international success of local industries. Based upon the regional distribution of comparative advantages, chapter 5 reports the results of ten regional case studies. Finally, chapter 6 summarises the results and provides policy implications.
Additional information: Prepared for: European Commission - Executive Agency for Small and Medium-sized Enterprises (EASME)
Keywords: 330; SMEs; Comparative advantage; Export economy; Regional economics; EU states; KMU; Komparativer Vorteil; Exportwirtschaft; Regionalökonomik; EU-Staaten